1995
DOI: 10.1177/026765919501000107
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vascular pressure and different primes on the fluid balance of, and oxygen supply to, the patient during CABG

Abstract: Detrimental changes of blood and erythrocyte rheology, and fluid exchange between the vascular and interstitial spaces, which influence the rate that oxygen is supplied to the patient, occur during cardiac bypass surgery. Venous flow is subject to a pulsatile and uncertain variation, because the vena cava is more than 30 mmHg below atmospheric pressure. This occurs because the patient is about 1 m above the air-blood surface of the bypass reservoir. Before any reliable study of fluid exchange can be undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…24,25 Otherwise, at lower arterial blood pressures during CBP-related surgery, the reduction of plasma oncotic pressure using crystalloid priming is beneficial: the cited study showed that optimal oxygen exchange is achieved by the equilibration of plasma oncotic pressure and capillary hydrostatic pressure without altering the interstitial fluid volume. 26 Lactate accumulation as a surrogate parameter for tissue perfusion and oxygenation 27 is described as being reduced by RAP. 28 Although lactate levels were higher in patients treated with crystalloid compared with albumin 12 hours after surgery in our study, the difference was marginal and similar levels were observed at other time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Otherwise, at lower arterial blood pressures during CBP-related surgery, the reduction of plasma oncotic pressure using crystalloid priming is beneficial: the cited study showed that optimal oxygen exchange is achieved by the equilibration of plasma oncotic pressure and capillary hydrostatic pressure without altering the interstitial fluid volume. 26 Lactate accumulation as a surrogate parameter for tissue perfusion and oxygenation 27 is described as being reduced by RAP. 28 Although lactate levels were higher in patients treated with crystalloid compared with albumin 12 hours after surgery in our study, the difference was marginal and similar levels were observed at other time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the use of cardiopulmonary bypass (CPB) is associated with the development of significant systemic inflammatory response syndrome (SIRS) (57,58) which can affect patient outcomes. SIRS is characterized by high cardiac output, low mean and systolic blood pressure, low systemic vascular resistance, and a core temperature greater than 38°C or less than 36°C in the immediate postoperative period.…”
Section: Platelet Inhibition and Cardiopulmonary Bypassmentioning
confidence: 99%
“… 10 In contrast, an increased oncotic pressure is beneficial for maintaining a sufficient mean arterial pressure (MAP) and has been shown to improve organ perfusion. 11 As a consequence, colloids such as human albumin (HA) or hydroxyethyl starch (HES) are often added to the priming solution of the HLM. 12 13 However, a clear advantage for using colloidal solutions could not be demonstrated.…”
Section: Introductionmentioning
confidence: 99%